2017
DOI: 10.1111/coa.13031
|View full text |Cite
|
Sign up to set email alerts
|

Sino‐Nasal Outcome Test‐22 quality‐of‐life patterns in patients presenting with nasal septal perforation

Abstract: This study has assessed the clinimetric and psychometric properties of patients suffering from symptomatic NSP. Future reports should consider inclusion of SNOT-22 data but with the addition of perforation-specific symptoms (nasal crusting, epistaxis, whistling noise).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 14 publications
0
23
1
1
Order By: Relevance
“…For example, patients with cocaine-induced NSP may suffer from concomitant atrophic rhinitis and are likely to have increased rhinologic and facial symptoms, which can be compounded by the presence of NSP. 5 Data from this study showed that size of NSP measured by area (cm 2 ) did not demonstrate consistent correlation with total SNOT-22 and NSP-specific domain scores. However, wider A-P diameter and more posteriorly placed NSP resulted in a reduction in total SNOT-22 scores and NSP-specific symptoms, although these were only statistically significant for the latter.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…For example, patients with cocaine-induced NSP may suffer from concomitant atrophic rhinitis and are likely to have increased rhinologic and facial symptoms, which can be compounded by the presence of NSP. 5 Data from this study showed that size of NSP measured by area (cm 2 ) did not demonstrate consistent correlation with total SNOT-22 and NSP-specific domain scores. However, wider A-P diameter and more posteriorly placed NSP resulted in a reduction in total SNOT-22 scores and NSP-specific symptoms, although these were only statistically significant for the latter.…”
Section: Discussioncontrasting
confidence: 59%
“…The mean total SNOT-22 score observed in this study was comparable to other patients diagnosed with CRS, empty nose syndrome, or neurogenic facial pain syndromes. 4,5,9,10 Changes in nasal aerodynamics as a result of the nasal septal defect, coupled with alterations in nasal physiological function and preexisting mucosal disease, may provide some explanation to the etiology of complex sinonasal symptoms and affected well-being observed in this patient group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And SNOT-22 version is not yet fully content valid for NSD patients because other nasal symptoms common to NSD patients, such as epistaxis, which we added into our questionnaire, are not included in the current SNOT-22 architecture. Therefore, previous study suggests that further studies be performed to improve the SNOT score ( Leong & Webb, 2018 ).…”
Section: Discussionmentioning
confidence: 99%